PERBAIKAN MUTU BERKELANJUTAN (CONTINUOUS IMPROVEMENT) DAN STANDAR MUTU (QUALITY STANDART) DALAM PENDIDIKAN AGAMA ISLAM - Puspita, Kurnia Tri; Muallimin; Khoirul Anwar (JCI Publisher, 2026)
Islamic Religious Education (PAI) faces complex challenges in maintaining relevance and quality amidst social change, technology, and demands for public accountability. Two main concepts in educational quality management—continuous improvement and quality assurance—are often discussed separately, despite their fundamentally synergistic relationship. This study aims to conceptually examine the integration of continuous improvement and quality assurance in the context of PAI, addressing how both frameworks can be operationalized simultaneously to improve the quality of PAI delivery. Using a systematic literature review method through Google Scholar and Publish or Perish (PoP) for the 2019–2026 period, 25 relevant articles were analyzed from 80 initial findings. The results show that quality assurance functions as a holding system that establishes standards, while continuous improvement acts as a driving force encouraging innovation and adaptation. However, in PAI practice, tension exists between standard compliance (QA) and the need for dynamic change (CI). This article offers an integrative framework called the Adaptive Quality Cycle (AQC), combining the Plan-Do-Check-Act cycle with Islamic principles such as muhasabah (self-evaluation), tahsin (continuous improvement), and itqan (professionalism). This integration is key for PAI institutions to not only meet minimum standards but also continuously develop dynamically without losing their Islamic identity.